Annual Plan 1998-99 Volume III Statement of Schemewise Plan Outlay National Capital Territory of Delhi - Planning Commission (Planning Commission, 1998)
Financial Outlays, Physical Target, Basic Minimum Services, Centrally Sponsored Scheme, EAP Funding.
Planning-Department, National Capital Territory of Delhi